Blue Energy dari Mikroalga Chlorella sp. sebagai Bahan Baku Biodiesel - Rheamyta Carissa Siregar; Mahmiah (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2023)
Biodiesel is a renewable clean bioenergy because it can be produced from vegetable oil. One of the efforts to increase energy independence in the marine sector (blue energy) is to prepare potential alternative fuels derived from microalgae. Microalgae have advantages over other types of plants, because the growth of microalgae is very productive and the growth rate is very fast and does not require fertile land, so it does not compete with food crops. Some microalgae have an oil content of up to 80% of their body mass. Aims to provide information about differences in extraction methods and identification of oil content with microalgae type Chlorella sp. which can be used as raw material for biodiesel. This research method uses FTIR (Fourier Transform Infrared) and GC-MS (Gas Chromatography-Mass Spectrometry) analysis. The results showed that the soxhlet extraction method was able to separate biodiesel and to identify biodiesel raw materials, the percentage of microalgae oil and compound content was obtained. The most dominant compounds are Linoleic Acid compounds, Palmitic Acid compounds, which are dominated by Stearic Acid compounds.